Media, Journalism, and the Public Sphere in Private Family Ownership. On the Critique of the Political Economy of Capitalist Media Enterprises - Manfred Knoche (tripleC: Communication, Capitalism & Critique)
In the context of a Critique of the Political Economy of the Media, this article exemplifies the fundamental effects of the globally dominant capitalist private ownership of media companies on media development, journalism, and the public sphere. Selected works by Marx and Engels as well as works from developments of the approaches of the “New Reading of Marx” and “Western Marxism” form the theoretical-methodological basis. Characteristic of capitalism is a mutually conditioning relationship between the socio-economic base and the political-legal superstructure, which makes the ”abolition” of private property and the associated relations of domination and power almost impossible. Therefore, possibilities of a de-capitalisation and de-commodification of journalism and the public sphere based on non-capitalist forms of ownership will be discussed. A special chance of realisation is seen for academic publications without capitalist publishing houses that is feasible because knowledge production takes place at public universities. Finally, a change of strategy is suggested that takes us out of the bourgeois-liberal trap of criticism and hope towards the development of media and social theories as well as humans’ active participation in the organisation of an independent content-based media praxis, which can be conducive to a transformation towards a socialist societal formation.